Curricular structure and pedagogical approaches in pre-service physical education teacher education: a comparative case study of three Chilean universities - Gallardo-Fuentes, Francisco; Carter-Thuillier, Bastian; Rivas-Valenzuela, Johan; Cárdenas-Saldaña, Norma; Peña-Troncoso, Sebastián; Gallardo-Fuentes, Jorge; Añazco-Martínez, Luis (Frontiers in Education, 2025)
Physical education is recognized as a key discipline within the educational system due to its contribution to students’ holistic development across physical, cognitive, social, and emotional dimensions. Therefore, pre-service physical education teacher education (PETE) holds special relevance, as it shapes the pedagogical approach that will guide future teaching practices in the school. The objective of this study was to analyze the curricular structure and pedagogical approach of PETE programs at three Chilean universities. Using a qualitative-descriptive approach, a document analysis was conducted on curricula, graduate profiles, and course syllabi from each institution, considering that these are also key elements evaluated in the accreditation processes of teacher education programs. Grounded Theory supported the analysis, which was systematized using NVivo software through open and axial coding. The information was organized into key categories: subjects, graduate competencies, pedagogical approach, innovation, sociocultural context, and assessment. The results reveal differences in how teacher education is understood. While one university presents a structure focused on technical content, another emphasizes a sociocultural approach, and the third exhibits an innovative orientation with technological integration.